Humic Like Substances (HULIS): Contribution to Global Warming and Stratospheric Ozone Depletion - Whiteside, Mark; Herndon, J. Marvin (European Journal of Applied Sciences, 2023)
The authors have previously provided compelling evidence that coal fly ash particles, not chlorofluorocarbons (CFC’s), are the primary cause of stratospheric ozone depletion. Coal burning and coal fly ash aerosols utilized in covert tropospheric geoengineering have already severely damaged the stratospheric ozone layer, leading to deadly ultraviolet radiation UV-B and UV-C penetrating to Earth’s surface. Coal burning and biomass burning are primary sources of a particular organic aerosol, humic-like substances, referred to collectively as HULIS. HULIS, like coal fly ash, plays a key role in climate change due to its ubiquity in biogenic and anthropogenic aerosols, its ability to absorb solar ultraviolet radiation and to transfer that heat to atmospheric gases, which reduces the temperature difference relative to the near-surface air, which reduces atmospheric convection, and which concomitantly reduces heat loss from the surface, causing regional and global warming. HULIS affects human and environmental health by production of reactive oxygen species and environmentally persistent free radicals. Stratospheric ozone was apparently depleted during the Permian Extinction by coal and biomass combustion aerosols produced by massive volcanic activity. A spike in sea and land temperature during World War II, associated with particulate pollution, also is correlated with a spike in HULIS obtained from Alpine ice cores. Recently, large forest fires have also been shown to deplete stratospheric ozone. Since HULIS is common to both coal and biomass burning, and ozone is taken up by submicron HULIS particles, it follows that HULIS aerosols are another cause of stratospheric ozone depletion. Our time is short to end all geoengineering activities and reduce or eliminate anthropogenic coal fly ash and HULIS-type aerosols.